Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1104/pp.112.202853
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis in Arabidopsis Reveals Shoot- and Root-Specific Targets of Cytokinin Action and Differential Regulation of Hormonal Homeostasis    

Abstract: Republic, CZ-165 02 Prague, Czech Republic (B.P., J.M.)The plant hormones cytokinins (CKs) regulate multiple developmental and physiological processes in Arabidopsis (Arabidopsis thaliana). Responses to CKs vary in different organs and tissues (e.g. the response to CKs has been shown to be opposite in shoot and root samples). However, the tissue-specific targets of CKs and the mechanisms underlying such specificity remain largely unclear. Here, we show that the Arabidopsis proteome responds with strong tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 60 publications
1
29
1
1
Order By: Relevance
“…In Arabidopsis, endogenous cytokinins promoted ABA accumulation but suppressed ABA response (Nishiyama et al, 2011), and the cytokinin receptors HIS KINASE2, HIS KINASE3, and CYTOKININ RESPONSE1 were shown to negatively regulate ABA response in Arabidopsis germination assays (Tran et al, 2007). Another study demonstrated that application of the cytokinin 6-benzylaminopurine transiently increased Arabidopsis shoot ABA levels ( Zd'árská et al, 2013), while overexpression of the cytokinin biosynthesis enzyme isopentenyl transferase resulted in reduced ABA accumulation in petunia flowers (Chang et al, 2003). Overall, the existing evidence may suggest that it is more probable that some of the effects of cytokinins are transduced by ABA rather than vice versa.…”
Section: Aba Was Not Found To Strongly Influence Sugar or Cytokinin Pmentioning
confidence: 99%
“…In Arabidopsis, endogenous cytokinins promoted ABA accumulation but suppressed ABA response (Nishiyama et al, 2011), and the cytokinin receptors HIS KINASE2, HIS KINASE3, and CYTOKININ RESPONSE1 were shown to negatively regulate ABA response in Arabidopsis germination assays (Tran et al, 2007). Another study demonstrated that application of the cytokinin 6-benzylaminopurine transiently increased Arabidopsis shoot ABA levels ( Zd'árská et al, 2013), while overexpression of the cytokinin biosynthesis enzyme isopentenyl transferase resulted in reduced ABA accumulation in petunia flowers (Chang et al, 2003). Overall, the existing evidence may suggest that it is more probable that some of the effects of cytokinins are transduced by ABA rather than vice versa.…”
Section: Aba Was Not Found To Strongly Influence Sugar or Cytokinin Pmentioning
confidence: 99%
“…Originally, it was shown that CKs inhibit root growth and that this inhibition was mediated via the ethylene signaling pathway (Cary et al, 1995). Furthermore, CKs can induce ethylene biosynthesis by stabilizing ACS5 protein levels (Chae et al, 2003), resulting in a higher endogenous ACC content ( Zd'árská et al, 2013). CKs also up-regulate the levels of S-adenosyl methionine synthetase and ACO in the root ( Zd'árská et al, 2013), most likely leading to a local increase in ethylene production and, consequently, to the inhibition of root elongation.…”
Section: Ethylene Cross Talk During Primary Root Growthmentioning
confidence: 99%
“…Furthermore, CKs can induce ethylene biosynthesis by stabilizing ACS5 protein levels (Chae et al, 2003), resulting in a higher endogenous ACC content ( Zd'árská et al, 2013). CKs also up-regulate the levels of S-adenosyl methionine synthetase and ACO in the root ( Zd'árská et al, 2013), most likely leading to a local increase in ethylene production and, consequently, to the inhibition of root elongation. Contradictorily, Kushwah et al (2011) showed that CKs can induce root elongation instead of inhibition and that this response is also mediated by the ethylene signaling pathway.…”
Section: Ethylene Cross Talk During Primary Root Growthmentioning
confidence: 99%
“…Cytokinin also induces ethylene biosynthesis (Vogel et al, 1998a(Vogel et al, , 1998bChae et al, 2003;Hansen et al, 2009;Zd'árská et al, 2013), raising the possibility that the inhibitory effect of cytokinin on cell proliferation might exhibit ethylene dependence. We, therefore, examined the RAM response to the cytokinin benzyladenine (BA) in the wild type, the ethylene-insensitive mutants etr1-1 and ein2-1, and the constitutive ethylene-response mutant ctr1-2 (Fig.…”
Section: Ethylene Facilitates Cytokinin Regulation Of Root Meristem Sizementioning
confidence: 99%